Analisis Kualitas Air di Perairan Danau Sentani Kampung Asei Kecil, Distrik Sentani Timur, Kabupaten Jayapura - Ciana Magdalena Morin; Fuad Muhammad; Maryono Maryono (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
Sentani Lake in Papua Province is a significant ecosystem with multiple functions as ecological, economic, tourism, and transportation purposes. Unfortunately, the lake has been subject to pollution and damage due to human activities which degrade the riparian and water catchment areas, declining the endemic fauna. Settlements, transportation, agriculture, mining, and floating net cage cultivation (KJA) for fishery purposes also contribute to the decrease in water quality. In this study, in-site and ex-site water analysis was performed to assess the water quality and pollution status of Sentani Lake. The pollution index (IP) was used as the parameter of water quality status and pollution level. Some parameters were assessed: temperature (30.4 oC – 33.3 oC), total suspended solids (TSS) (70 – 89 mg/l), clarity (1 m - 5.2 m), pH (8.36 - 8.48), dissolved oxygen (DO) (5.74 mg/l – 6.43 mg/l), biochemical oxygen demand (BOD) (0.21 mg/l - 2.11 mg/l), chemical oxygen demand (COD) (20.0 mg/l - 30.0 mg/l), phosphate (0.36 mg/l – 1.54 mg/l), and nitrogen (0.47 mg/l – 0.98 mg/l). During the day, the temperature ranged from 31.0 oC – 32.0 oC, TSS (72 – 93 mg/l), clarity (1.2 m - 4.5 m), pH (8.28 – 8.40), DO (6.21 mg/l – 6.82 mg/l), BOD (1.01 mg/l – 2.62 mg/l), COD (20.0 mg/l – 35.0 mg/l), phosphate (0.21 mg/l – 1.22 mg/l), and nitrogen (0.48 mg/l – 0.87 mg/l). Overall, the water quality was moderately polluted, with IP values ranging from 6.373 to 8.605 in the morning and from 5.553 to 7.946 in the afternoon.